Os jovens negros e universitários moradores da periferia da cidade de São Paulo: expectativas, conflitos e contradições - Tineu, Rogerio (2019)
The aim of this study is to focus on the study of life expectancy, the social conflicts and contradictions originated from racism and socio-spatial segregation experienced by the black population in the city of São Paulo, especially the young black college students from private institutions who live on the outskirts. The city of São Paulo presents itself divided in two areas in schematic form, the one that consists eminently of white individuals, it is located in the southwestern part of the city and it develops a role of dynamic socioeconomic center. Around this center, the population consists mostly of poor black individuals. From this social urban division, it is possible to notice a matter of race and social class, the production of the other and different one, this is the aim of this research. Students from private universities amplify their racial awareness or look for graduation only for an economic perspective, who are these young people and what are their expectations, conflicts and difficulties, is the university inclusive or only a place for the white, does the university represent this division of the city of São Paulo, those are some of the questions that guide this study. The importance of his investigation relies on the fact that there has been a significant increase of black people at Brazilian universities for the past fifteen years through various public policies, what, probably, produces a generation of young black people that understand better their apace of struggle. The methodology of research focuses on four non structured interviews and a sample composed of 225 questionnaires applied to black college students from private institutions (two in particular is communities, the PUC-SP and Fundação Cásper Líbero) in the city of São Paulo. The universities are separated in two types, the popular ones that are positioned as commodities and charge more affordable tuitions and the elitist ones charge higher tuitions. The data analysis allowed us, among other things, to describe a sample of profile, compare data and information among the students of both kinds of institutions and the participant and non-participant students of social movements, besides crossing information to the ones obtained in the non-structured interviews. Synthetically, the students recognize they have experienced racism, but they feel proud of their black origin, being black is to struggle daily for their rights and that requires harder work. It is inferred, therefore, that the university is inclusive and it developed their racial and class awareness, although this was an unknown path for them and their family, however, there are still challenges to be overcome